Unveiling the effects of substituents on the packing motif and the carrier transport of dinaphtho-thieno-thiophene (DNTT)-based materials. (14th June 2021) - Lin, Pan-Pan; Qin, Gui-Ya; Guo, Jing-Fu; Zhang, Bo-Hua; Li, Hui-Yuan; Zou, Lu-Yi; Ren, Ai-Min
Abstract : The impacts of intermolecular interactions on packing motifs and substitution positions on charge transport properties are elaborately delineated based on four crystal structures of dinaphtho-thieno-thiophene (DNTT) derivatives predicted by USPEX. Abstract : Molecular modification plays an important role in tuning the packing motif and charge transport in organic semiconductor materials. In particular, electron-withdrawing substituents and functional heteroatoms have seen a recent surge of interest. Here, we modeled four crystal structures of dinaphtho-thieno-thiophene (DNTT ) derivatives with the trifluoromethyl (–CF3 ) group and heteroatoms (O- and N-atoms), and elaborately delineated the impact of intermolecular interactions to establish the relationship between microscopic molecular structures and macroscopic solid-state packing. The effects of –CF3, O-, and N-atom positions on the charge transport properties were systematically investigated via multi-scale theoretical simulations. The results show that the reorganization energy and frontier molecular orbital energy levels are more sensitive to the positions of O- and N-atoms than the –CF3 position. Significantly, the substitution of heteroatoms on the terminal benzene ring can lead to ambipolar materials after introducing –CF3 . The cooperative effect of –CF3, O-, and N-atom substitution can transform the molecular packing from herringbone-stacking to π-stacking. The simultaneous introduction of –CF3 in the trans -position and O-, and N-atoms in the terminal benzene ring can bring the most compact packing and more hydrogen bonds. Besides, the transfer integral fluctuation caused by the position of –CF3 is more intense than that of O- and N-atoms, which originated from the long- and short-axis sliding motions that act as "killer" phonon modes. Our work shows that suitable substituent engineering on p-channel materials might simultaneously realize changes in molecular packing and carrier transport, paving the way toward designing higher-performance specific ambipolar transport materials.